A Study on Reproductive Rights and Abortion Laws (Journal of Advances and Scholarly Researches in Allied Education, 2026)
Within the context of modern legal, medical, ethical, and human rights debate, abortion continues to be one of the most delicate and contentious subjects under discussion. A difficult balance must be struck between women's reproductive autonomy, constitutional rights, medical ethics, concerns about public health, and the preservation of foetal life when it comes to the control of abortion legislation. This article takes a look at the legal framework that governs abortion in both India and the United States, with a specific focus on reproductive rights, constitutional protection, and current advances in the legal system. In addition, the paper discusses important obstacles that are associated with abortion regulations. These issues include societal stigma, poor healthcare facilities, legal uncertainty, political disputes, and uneven access to safe abortion services.